ANALISIS SIFAT FISIK BIJI KAKAO PADA BERBAGAI METODE FERMENTASI DAN KONSENTRASI FERMIPAN - Alfred Patty (JURNAL HUTAN PULAU-PULAU KECIL, 2019)
This research was done to analyze physical properties of fermented cocoa beans using various fermentation methods and fermipan concentrations. The aim of this study was to identify effective fermentation methods to produce quality cocoa beans. For each trial 10 kg of fresh cocoa beans were treated with fermipan in concentrations 0.5% w/v and 1% w/v. Fermentation trials were conducted in wooden boxes, plastic baskets and in heaps without turning the materials. The trials were conducted aerobically at room temperature for the next 6 days (144 hours). The results showed that the cocoa bean temperature increased significantly the 24th hour of fermentation and then slowly decreased until the end of the fermentation period except for the beans in heaps. The highest temperature of 42oC was found in beans in wooden boxes using the 1% w/v fermipan concentration. During fermentation, the pH of the pulp increased according to the period of fermentation and reached a peak at 144 hour. The highest pH was 7.02 found in beans placed in plastic baskets with 1% w/v of fermipan concentration. Overall the cocoa beans which fermented in wooden boxes with 1% w/v of fermipan gave the best quality with shell content of 15.05 %, brown color intensity of 90%, unfermented beans 2%, insect infestation 1.14% and beans germinated 1.90%.